Promoter type influences transcriptional topography by targeting genes to distinct nucleoplasmic sites. - Larkin, J; Papantonis, A; Cook, P (2013)
Both the sequence of a promoter and the position of a gene in 3D nuclear space play crucial roles in gene regulation, but few studies address their inter-relationship. Using human and viral promoters on mini-chromosomes and RNA fluorescence in situ hybridization coupled to 'high-precision' localization, we show that promoters binding the same transcription factors and responding to the same signaling pathways tend to be co-transcribed in the same transcription factories. We go on to suggest how such spatial co-association might drive co-regulation of genes under the control of similar cis-elements.